Reconstruction of tax balance sheets based on IFRS information: A case study of listed companies within Austria, Germany, and the Netherlands - Rebekka Kager; Rainer Niemann (Arbeitskreis Quantitative Steuerlehre (arqus), 2011)
The internationalisation of financial accounting and the European Commission's ambition to harmonise corporate taxation have raised the question whether IFRS accounts could be used for tax purposes. In order to quantify the effect of an IFRS-based taxation on corporate tax burdens in different EU member states, we estimate firms' tax equity using notes on income taxes in IFRS financial statements of companies listed in Austria, Germany, and the Netherlands. The difference between estimated tax equity and IFRS-equity, adjusted for the effect resulting from the recognition of deferred taxes, indicates the effect of using IFRS as a tax base on corporate tax burden. We find that estimated tax equity is mostly lower than IFRSequity, indicating that an IFRS-based taxation would often increase the corporate tax burden. The median of estimated tax equity is 5.6% (Austria), 6.4% (Germany) and 9.0% (the Netherlands) below IFRS-equity. Our results suggest that using IFRS for the determination of taxable income would often increase corporate tax burden. However, an IFRS-based taxation does not always induce higher equity as often argued in the literature. In 307 of 1.113 totally analysed firm-years, estimated tax equity exceeds IFRS-equity. Analysing IFRS-tax differences on a balance sheet caption level, we find that the most important differences can be observed for intangibles and provisions. We find for all three analysed countries that IFRS-tax differences relating to inventories, receivables, and liabilities are typically small. We also approximate the total stock of unused tax losses and the amount of useable tax losses which can provide additional information about the management's estimates of future earnings. We find that deferred tax assets for unused tax losses are depreciated to a substantial extent, indicating that companies often assume insufficient future taxable income to utilise the total stock of tax loss carry-forwards.
Keywords: 330; Unternehmensbesteuerung; Steuerbemessung; International Financial Reporting Standards; Bilanzsteuerrecht; Steuerbelastung; Österreich; Deutschland; Niederlande